1972
DOI: 10.1111/j.1365-3059.1972.tb01755.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fruit Tree Red Spider Mite (Panonychus ulmi) on Yield of Apple Trees in Kent

Abstract: SUMMARY Yields of apple fruits over 55 mm or 2 1/4 in. in diameter of CV. Cox's Orange Pippin in orchards studied in Kent were significantly decreased in only two out of five years between 1965 and 1971 by infestations of fruit tree red spider mite. In both these years, early peak populations of the mite occurred before mid‐July.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1973
1973
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Data was scattered and no threshold was apparent in 1992 and 1994. These results are consistent with highly variable effects of ERM on apple fruit size previously reported Chapman et al, 1952;Hull and Beers, 1990;Lakso et al, 1996;Light and Ludlam, 1972;Marini et al, 1994;Zwick et al, 1976).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Data was scattered and no threshold was apparent in 1992 and 1994. These results are consistent with highly variable effects of ERM on apple fruit size previously reported Chapman et al, 1952;Hull and Beers, 1990;Lakso et al, 1996;Light and Ludlam, 1972;Marini et al, 1994;Zwick et al, 1976).…”
Section: Resultssupporting
confidence: 92%
“…ERM injury causes reduced leaf net CO 2 exchange rate (NCER) Lakso et al, 1996;Mobley and Marini, 1990) and can reduce yield, fruit size and quality, and return bloom (Ames et al, 1984;Chapman et al, 1952;Coghill, 1969;Hull and Beers, 1990;Lakso et al, 1996;Lienk and Minns, 1980;Light and Ludlam, 1972;Marini et al, 1994;Redl et al, 1991;Zwick et al, 1976). Results in these individual studies varied considerably, probably due to differences in the environment, the timing and ated.…”
mentioning
confidence: 99%
“…Klopfenstein (17), Zwick et al (27), and Ames et al (10), on the other hand, found no reduction in fruit size. Return bloom has been reported by some (2,18,19) to be reduced greatly by mite damage, while others (6,20,27) found no effect. Hoyt et al (16) reported no effect when mite populations occurred mid-season on vigorous trees, but pointed out that the timing of damage may be a crucial factor.…”
Section: Bloom With Moderate To High Mite Damage Regardless Ofmentioning
confidence: 92%
“…The experimental design was a completely randomized 2 x 4 factorial treatment arrangement replicated six times, with two mite damage levels (check = 0 cumulative mite days and high = 1500 cumulative mite days) applied over four LFRs (20,30,50, and 70 leaves per fruit). Mite days are defined as one mite (per leaf) present for 1 day, and calculated as the mean of two successive counts (i.e., mean number of mites per leaf) multiplied by the number of intervening days.…”
Section: Methodsmentioning
confidence: 99%
“…This damage leads to a variety of current-year and second-year effects. Current-year damage, depending on the timing, duration, and severity of the damage, can lead to reduced levels of foliar nitrogen (Klopfenstein and Holdsworth 1978) and other essential elements (Ames et al 1984;Herbert and Butler 1973), premature leaf fall (Baker 1984), reduced growth of shoots (Briggs and Avery 1968) and of trunk diameter (Chapman et al 1952), fewer fruit and lower yields (Light and Ludlam 1972;Baker 1984;Chapman et al 1952), and adverse effects on fruit size (Hoyt et al 1979;Baker 1984), skin color, soluble solids, titratable acids, and firmness (Ames et al 1984). Ames et al (1984) also found a significant interaction between fruit load and mite effects on spur-type Red Delicious apple trees.…”
Section: Introductionmentioning
confidence: 99%